2001
DOI: 10.1175/1520-0434(2001)016<0697:eeonal>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Error Evaluation of NCEP and LAHM Regional Model Daily Forecasts over Southern South America

Abstract: NCEP short-range operational forecast and Limited Area HIBU (Federal Hydrometeorological Institute and Belgrade University) Model (LAHM) regional model performance during a 2-month period over the southern part of South America are evaluated through the analysis of bias and rmse's. While spatial structure of errors could be only examined using gridded operational analyses as the ''ground truth,'' observed data have been used at two radiosonde stations to have an independent control of forecast and analysis qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
7
0
4
Order By: Relevance
“…In other cases, such as in the product considered in this paper, it is only considered whether or not rain or snow is likely to happen without worrying about intensity or quantity. Clearly, it is necessary to establish a different treatment of the data depending on the kind of event considered here, because low and high intensity precipitation events are not equally predictable and detectable (Saulo and Ferreira, 2003), so their derived scores may be completely different.…”
Section: Influence Of the Low Intensity Precipitation Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cases, such as in the product considered in this paper, it is only considered whether or not rain or snow is likely to happen without worrying about intensity or quantity. Clearly, it is necessary to establish a different treatment of the data depending on the kind of event considered here, because low and high intensity precipitation events are not equally predictable and detectable (Saulo and Ferreira, 2003), so their derived scores may be completely different.…”
Section: Influence Of the Low Intensity Precipitation Eventsmentioning
confidence: 99%
“…The lack of representativeness of a station net is a sensitive problem in many aspects of meteorology, such as weather modelling (Tustison et al, 2001), assimilation (Bock et al, 2005) and verification (Arteaga-Ramirez et al, 2004). However, it is especially crucial in those physical fields such as precipitation that are highly discontinuous in space and time (Saulo and Ferreira, 2003) or in those regions where data availability is scarce Yang and Woo, 1999;Woo and Young, 2004). Therefore, when the spatial representativeness of the observational data is not complete because the observed and forecasted fields do not cover the same region, significant biases may be introduced in the calculated scores and results.…”
Section: Introductionmentioning
confidence: 99%
“…However, deficiencies are observed, particularly in rainfall forecast. Saulo et al (2001) and Saulo and Ferreira (2003), identified rainfall deficits in the forecasts for the northern part of the La Plata Basin. In addition, the scarcity of data makes it difficult to assess model performance.…”
Section: Introductionmentioning
confidence: 96%
“…There is a general consensus that because of the difficulty in simulating these convective scale events the models underestimate the mean precipitation and yet overestimate the number of precipitation events (see, e.g., Rauscher et al 2007;Menéndez et al 2010). Second, the presence of the steep Andes Mountains to the west is poorly handled in the models, resulting in temperature and precipitation biases not only over and near the mountains but also downstream (Seluchi et al 1998;Saulo et al 2001;Chou et al 2005;Müller et al 2014). Finally, an accurate representation of the South American low-level jet and its associated moisture flux convergence is required to reproduce the precipitation spatial structure and diurnal cycle (see, e.g., Berbery and Collini 2000;Collini et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other short-term forecasts are systematically performed at academic institutions serving the needs of the local community. As with the models run in operational environments, these simulations present systematic errors like the overestimation of the frequency of low-intensity precipitation events and the underestimation of heavy rainfall events (see, .e.g., Saulo et al 2008;García Skabar et al 2012).…”
Section: Introductionmentioning
confidence: 99%